A critical role of cardiac fibroblast-derived exosomes in activating renin angiotensin system in cardiomyocytes. (December 2015) - Lyu, Linmao; Wang, Hui; Li, Bin; Qin, Qingyun; Qi, Lei; Nagarkatti, Mitzi; Nagarkatti, Prakash; Janicki, Joseph S.; Wang, Xing Li; Cui, Taixing
Abstract: Chronic activation of the myocardial renin angiotensin system (RAS) elevates the local level of angiotensin II (Ang II) thereby inducing pathological cardiac hypertrophy, which contributes to heart failure. However, the precise underlying mechanisms have not been fully delineated. Herein we report a novel paracrine mechanism between cardiac fibroblasts (CF)s and cardiomyocytes whereby Ang II induces pathological cardiac hypertrophy. In cultured CFs, Ang II treatment enhanced exosome release via the activation of Ang II receptor types 1 (AT1 R) and 2 (AT2 R), whereas lipopolysaccharide, insulin, endothelin (ET)-1, transforming growth factor beta (TGFβ)1 or hydrogen peroxide did not. The CF-derived exosomes upregulated the expression of renin, angiotensinogen, AT1 R, and AT2 R, downregulated angiotensin-converting enzyme 2, and enhanced Ang II production in cultured cardiomyocytes. In addition, the CF exosome-induced cardiomyocyte hypertrophy was blocked by both AT1 R and AT2 R antagonists. Exosome inhibitors, GW4869 and dimethyl amiloride (DMA), inhibited CF-induced cardiomyocyte hypertrophy with little effect on Ang II-induced cardiomyocyte hypertrophy. Mechanistically, CF exosomes upregulated RAS in cardiomyocytes via the activation of mitogen-activated protein kinases (MAPKs) and Akt. Finally, Ang II-induced exosome release from cardiac fibroblasts and pathological cardiac hypertrophy were dramatically inhibited by GW4869 and DMA in mice. These findings demonstrate that Ang II stimulates CFs to release exosomes, which in turn increase Ang II production and its receptor expression in cardiomyocytes, thereby intensifying Ang II-induced pathological cardiac hypertrophy. Accordingly, specific targeting of Ang II-induced exosome release from CFs may serve as a novel therapeutic approach to treat cardiac pathological hypertrophy and heart failure. Highlights: Ang II stimulates the release of exosomes from cardiac fibroblasts (CF exosomes). CF exosomes upregulate renin angiotensin system in cardiomyocytes. CF exosomes induce cardiomyocyte hypertrophy via activating AT1 R and AT2 R. Ang II-induced cardiac hypertrophy is inhibited by suppression of exosome production.